Combined adsorption and oxidation technique for waste water treatment: potential application in permeable reactive barrier - Shukla, Pradeep (Curtin University, 2010)
This dissertation explores a combined adsorption and advanced oxidation technology for trapping and destruction of organic pollutants in waste water. The adsorbed/immobilized pollutant onto the surface of metal supported catalyst is oxidized via advanced oxidation technology. The advanced oxidation process is carried out using Co[superscript]2+/KHSO[subscript]5 (Cobalt/peroxymonosulphate) reagent to generate highly active sulphate radical (SO[subscript]4*), which can readily attack and oxidize the organic pollutants in waste water. The reaction mechanism of Co[superscript]2+/KHSO[subscript]5 reagent follows similarly to the Fenton reagent (Fe[superscript]2+/H[subscript]2O[subscript]2) which is used to generate hydroxyl radical (OH*). Co[superscript]2+/KHSO[subscript]5 reagent has been successfully utilized for bleaching applications and oxidation of organic contaminants. Compared to hydroxyl radical, the sulphate radical is highly potent to oxidize contaminants even at basic pH. However the biggest disadvantage of using Co[superscript]2+/KHSO[subscript]5 reagent is the dissolution of Co[superscript]2+ ion into the water which poses a severe environmental hazard. In the current study, cobalt ion is incorporated into supporting media and utilized for advanced oxidation.Very few studies have so far explored the heterogeneous oxidation technology based on Co[superscript]2+/KHSO[subscript]5 for the treatment of organic contaminants in water. With this research focus, various support media have been utilized to load cobalt ions, which included Zeolite A, Zeolite X, ZSM-5, SBA-15, Silica and Activated Carbon. Cobalt metal was incorporated into commercial Zeolites by ion exchange technique whereas in-situ cobalt loading was carried out during the synthesis of SBA-15. Cobalt loading was done into Silica and Activated Carbon by conventional impregnation technique. The choice of cobalt loading technique inherently determines the oxidation state of cobalt species loaded into the sample which in turn determines the oxidation efficiency. Furthermore, the choice of cobalt precursor significantly affects the metal-support bonding which has been investigated by loading on silica support with different types of cobalt precursor such as cobalt chloride, cobalt acetate and cobalt nitrate. Many of these supports such as Zeolite ZSM-5 and Activated Carbon have never been tested before for cobalt loading and oxidation via sulphate based oxidant and demonstrate efficient oxidation of phenolic pollutants.The investigation of organic oxidation using sulphate based oxidants was further extended into photocatalytic reactions. Photo degradation was carried out using artificial solar light and germicidal UV radiation in the presence of ZnO and oxidants such as peroxymonosulphate, peroxidisulphate and hydrogen peroxide. The comparison of photochemical and photocatalytic oxidation was carried out and their synergy of combination was explored.The thesis provides a thorough exploration of heterogeneous oxidation via sulphate based oxidant for the treatment of organic pollutants. The supported catalysts investigated here can be further improved and utilized as a PRB media for groundwater remediation. A final chapter discusses about the mathematical modeling of a column test to mimic a lab scale PRB in order to investigate the process parameters affecting the PRB design. The column modeling also directs towards a development of a novel “Reactive Adsorber” for the treatment of industrial waste by combined adsorption and oxidation.